2019
DOI: 10.1101/539270
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cohesin occupancy and composition at enhancers and promoters are linked to DNA replication origin proximity inDrosophila

Abstract: Cohesin consists of the Smc1-Smc3-Rad21 tripartite ring and the SA protein that interacts with Rad21. The Nipped-B protein loads cohesin topologically around chromosomes to mediate sister chromatid cohesion and facilitate long-range control of gene transcription. It is largely unknown how Nipped-B and cohesin associate specifically with gene promoters and transcriptional enhancers, or how sister chromatid cohesion is established. Here we use genome-wide chromatin immunoprecipitation in Drosophila cells to show… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…In mESCs, cohesin and its loader Nipbl are found at promoters and enhancers, in addition to CTCF sites (Kagey et al, 2010). In yeast, the RSC chromatin remodeler recruits cohesin loading (Muñoz et al, 2019), while in Drosophila, DNA replication complexes have been implicated (Pherson et al, 2019). Another potential contributor is that the recruitment of RNA polymerase II to active enhancers increases the mobility of those loci, thereby increasing the frequency of longrange contacts (Gu et al, 2018).…”
Section: Architectural Stripesmentioning
confidence: 99%
“…In mESCs, cohesin and its loader Nipbl are found at promoters and enhancers, in addition to CTCF sites (Kagey et al, 2010). In yeast, the RSC chromatin remodeler recruits cohesin loading (Muñoz et al, 2019), while in Drosophila, DNA replication complexes have been implicated (Pherson et al, 2019). Another potential contributor is that the recruitment of RNA polymerase II to active enhancers increases the mobility of those loci, thereby increasing the frequency of longrange contacts (Gu et al, 2018).…”
Section: Architectural Stripesmentioning
confidence: 99%
“…Interestingly, recent studies have shown that cohesin is required for enhancer activity in mammalian systems, but mainly for long range enhancer activity [77,78]. We find that the 3D genome architecture might play a role in enhancer activity in Drosophila similarly to mammalian system [61].…”
Section: Associated Proteins At Enhancersmentioning
confidence: 54%
“…Due to the similarities in function of subunits of cohesin and the mediator complex we used a single track for each of the two complexes (Nipped-B for cohesin and MED1 for Mediator) to prevent rules involving cohesin or the mediator complex from becoming diluted across several features. In particular, Nipped-B and SA recruit cohesin to the genome and Rad21 and Smc1 are two cohesion subunits [61]. Fs(1)h was found to recruit Nipped-B [62] and, thus, was also not included in the selected features.…”
Section: Enrichment Of Proteins and Epigenetic Factors At Different Classes Of Enhancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cofactors are also required to establish physical contacts and anchor them to nuclear structures. In Drosophila , proteins such as the modifier of mdg4 (Mod (mdg4)) [ 191 , 192 ] and centrosomal protein of 190kDa (CP190) [ 193 ]; cohesins (like Rad21/Vtd); and condensins (like Cap-H2) are present in different combinations in all types of insulators and fulfill these functions [ 194 ].…”
Section: Hp1a Interaction With Insulator and Architectural Proteinmentioning
confidence: 99%